Outer Retinal Dysfunction on Multifocal Electroretinography May Help Differentiating Multiple Sclerosis From Neuromyelitis Optica Spectrum Disorder - Filgueiras, Thiago G.; Oyamada, Maria K.; Preti, Rony C.; Apóstolos-Pereira, Samira L.; Callegaro, Dagoberto; Monteiro, Mário L. R. (Frontiers in Neurology, 2019)
Purpose: To evaluate the intermediate and outer retina of patients with multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD) using OCT and multifocal electroretinography (mf-ERG) Methods: Patients with MS (n=30), NMOSD (n=30) and healthy controls (n=29) underwent visual field(VF), OCT and mf-ERG testing. The eyes were distributed into 5 groups: MS with or without history of ON (MS+ON, MS-ON), NMOSD with or without ON (NMOSD+ON, NMOSD-ON), and controls. The thickness of the macular retinal nerve fiber layer (mRNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), inner nuclear layer, outer plexiform layer, outer nuclear layer, and photoreceptor layer was measured. mf-ERG P1 and N1 responses were registered and grouped in 3 sets of rings. The groups were compared using GEE models, and effect size (ES) calculated. Results: Compared to controls, GCL and IPL thickness was significantly smaller in MS+ON (both p<0.01), MS-ON (p<0.01 and p=0.015, respectively), NMOSD+ON (both p<0.01) and NMOSD-ON (p=0.03 and p=0.018, respectively). ES was >0.80. mRNFL was smaller in three of the above groups (p<0.01, p<0.001 and p=0.028;ES>0.80) but not in MS-ON eyes (p=0.18). No significant difference was observed for the remaining layers. Compared to controls, P1 and N1 peak times were smaller in MS (p-values in the range 0.049-0.002, ES<0.50; and 0.049-0.010;ES<0.50, respectively) but not in NMOSD. These abnormalities were strongly correlated with intermediate and outer retinal layer thickness. Conclusions: mf-ERG data suggest outer retinal abnormalities in MS, but not in NMOSD. Our results may help understand how the two conditions differ regarding retinal damage.